The power of notes taking in a classroom: more than capturing the information / Hazwati Hashim - Hashim, Hazwati (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Taking notes while listening to a lecture or teacher’s talk has decreased and is drowning amongst the pile of technological devices. Some students perceive this way of learning as outdated, especially Generation Z and the newly emerging Gen Alpha, where they mostly prefer digital ready-made materials. These generations are too much dependent on using their smartphone to be used for snapping notes presented in the slides. Moreover, they find it much easier to record the lecture to be used later for revision or as a reference for the assignment. As a result of being pampered with technological devices, students tend to rely on these devices and refuse to focus on class. On the same token, the worst-case scenario is when they feel that the lesson is not important as they can follow up later on through reviewing the pictures taken earlier or through the recorded lesson. This scenario has made the students not appreciate lectures, and they will just sit in the class and somehow hope that the class will dismiss early as they no longer appreciate meeting the instructor in the class. Therefore, the instructors must know how to encourage the students to inculcate the habit of taking notes and some more share the benefits with the students.